Self-assembled Amphotericin B Pharmacosome like Vesicles Derived from Lipid-based Microtubes: a Model Carrier to Further Explore - Salerno, Claudia (2020)
Background: Self-assembled drug delivery systems are of much interest since they can be produced by simple low cost and solvent-free procedures. Pharmacosomes are supramolecular-structured nanocarriers with benefits for drug stability and targeting delivery. Amphotericin B (AmB) still remains an important agent for the treatment of invasive mold infections, e.g invasive aspergillo-sis, although the challenge for new formulations is still prevailing due to high rates of toxicity. Objective: We have previously reported the incorporation of AmB into 12-hydroxystearic acid lipid-based microtubes (MTs) for topical use, herein we report the ability of AmB-MTs to self-assemble into vesicles upon dilution. Methods: AmB-MTs with different drug concentrations (1, 3, 5 mg/ml) were prepared, and size de-termination was carried out for different dilutions. Morphology was evaluated by microscopy. In vitro cytotoxicity was evaluated in Vero cells and in vitro activity against Aspergillus fumigatus and Asper-gillus flavus was assessed. Results: AmB-MTs closed upon dilution to form vesicles ranging from 200 nm to 1µm. AmB MIC (Minimum inhibitory concentration) for both Aspergillus species was 0.0625 and 0.125 µg/ml for dis-persion and reconstituted lyophilized, respectively. Conclusion: AmB pharmacosome-like vesicles are smaller structures than MTs may thus be favoura-ble for other delivery routes. We assume that this kind of pharmacosomes-like carrier is a promising model for the obtention of new vesicular carriers based on lipid MTs.